VD_FINDINFO Jug / 2019 / 442 vom 19. März 2019 - VD Tribunal cantonal (2019)
ENLÈVEMENTINFRACTION, CONSTATATION DES FAITS, FIXATION DE LA PEINE, TORT MORAL | 49 CO, 25 CP, 42 al. 1 CP, 47 CP, 49 al. 1 CP, 10 CPP (CH)